COOKING WITH CONJUNCTION: A STUDY OF COHESION - I Wayan Juniartha (SPHOTA: Jurnal Linguistik dan Sastra, 2014)
ABSTRACT This article is entitled Cooking with Conjunction. It discusses about the Equivalence of conjunction in cookbooks. The shortness of imperative sentences in cook books sometimes makes the clauses are mostly jointed from one sentence to another using conjunction. It is very important in constructing the flow of the sentences so that it is easier to be translated. The objectives of this paper is to describe the shift of the types of conjunction, to explain the function of the conjunction both in the original text and translated text; and to analyze the potential meaning covered by the shift of types and conjunction. The theories used are: The theory of cohesion proposed by Halliday (1976) and the theory about conjunction and creation of text proposed by Halliday (1994). Another instrument used in translating the original text as a comparison to the translated text in the book is Google Translation Tools (GTT). After getting the meaning, data was analyzed by binding the data together with previous clauses and the clause after to see the intertwining of those clauses. The finding of the analysis shows that the translation of conjunction sometimes shifts into the different types and categories. Some types and the categories of conjunction are not explicitly translated; The function carried out by the translated conjunction in TL sometimes shift from the functions of the original conjunction written in the original text. The meanings of the conjunction that are translated into TL is not really different from the original text in SL. some suggestions which can be drawn are: type of conjunction which is implicitly written better be avoided, in order to create a clear cohesiveness to the text; the shifting of the type and function of conjunction in the translation text is natural as far as the meaning of the original text is kept by the shifting and never destroys the meaning of the original text. keywords: cook books; conjunction; shifting; equivalency; implicit